24 h-Heart Rate Variability as a Communication Tool for a Personalized Psychosomatic Consultation in Occupational Health - Jarczok, Marc N.; Buckley, Thomas; Guendel, Harald O.; Boeckelmann, Irina; Mauss, Daniel; Thayer, Julian F.; Balint, Elisabeth M. (Frontiers in Neuroscience, 2021)
New tools for non-specific primary prevention strategies covering somatic and mental health in occupational medicine are urgently needed. Heart rate variability (HRV) reflects the capacity of the body to adapt to environmental challenges and of the mind to regulate emotions. Hence, a 24h-measurement of HRV offers a unique possibility to quantify the interaction between situation-specific emotional regulation within a specific psychosocial environment and physiological state, thereby increasing self-perception and inducing motivation to change behavior. The focus of the present study represents such a 24h-measurement of HRV and its presentation as a comprehensive graph including protocolled situations of the client. A special training program for occupational health physicians and questionnaires for clients were developed and administered. The manuscript reports the first data of the study "healthy leadership and work - body signals for managers and employees”, an investigator-initiated, interventional, single-arm, open (non-blinded), multicenter, national trial with 168 participants. They reported a significantly improved perception of their bodily needs after the consultation (from Median=7, interquartile range 5-8 to Median=8, interquartile range 7-9; scale range from 1-10; p<0.001, Wilcoxon rank test; effect size .49). The sixteen occupational health physicians stated that the measurement of HRV was very well suited to enter into dialogue with the managers and was feasible to show interactions between situations, thoughts, feelings, and bodily reactions. Taken together, we show that a 24h-HRV-measurement can be a feasible and effective approach for holistic, psychosomatic primary prevention in occupational medicine. We discuss possible mechanisms for improving the individual health via the consultation, containing mindset and improved ANS activity.